Amorphous Iron Formation by Discontinuous Rubbing - H. Furuichi (New Approaches in Engineering Research Vol. 14, 2021)
A unidirectional dry rubbing in a low vacuum, regularly separating \(α\)-iron slider from \(α\)-iron specimen generated a layer of piled-up adhered wear debris whose thickness was more than 100 \(μ\)m. TEM diffraction patterns taken from this layer consist of large spots and halo rings. This seems to demonstrate the state just before the perfect amorphization. All the rings and spots correspond to the structure formed due to the occupancy of iron atoms in O and T sites of \(ε\)-iron. Neither this way of amorphization nor the occupied structure mentioned above has been reported. Both the amorphous state and the occupied structure remain at ambient conditions. The mechanism of high-pressure generation that transformed \(α\)-iron to \(ε\)-iron is presented.